A composite model for evaluating fatigue life of offshore wind turbines equipped with a tuned mass damper - McAuliffe, James; Broderick, Brian; Fitzgerald, Breiffni (CRC, 2025)
Driven by the need to enhance the energy density of individual units, modern wind turbines have undergone a substantial increase in both turbine scale and power rating, with a growing trend toward offshore construction. However, the corrosive marine environment and challenging conditions typical of offshore locations, coupled with greater self-loads, render modern wind turbines susceptible to fatigue damage. This study employs a composite model to conduct a local fatigue analysis of a fatigue critical component at the base of the state-of-the-art IEC 15-MW offshore wind turbine tower, specifically to investigate the influence of Tuned Mass Dampers (TMD) on the fatigue life of offshore wind turbines. The composite model utilises a blended modelling approach integrating a holistic multibody dynamic model and a detailed finite element model, leveraging the strengths of both approaches to deliver an efficient and accurate fatigue analysis of the turbine mitigating the inherent weaknesses of each individual model. The multibody dynamic model, fully cou- pled with 22 degrees of freedom, developed using Kane’s Dynamics is employed within this composite model to simulate nominal stress time histories of the wind turbine subjected to environmental loading, considering the effects of both hydrodynamic and aerodynamic loading. The detailed finite element model is constructed to calculate Stress Concentration Factors (SCF) in fatigue-critical locations which can be combined with the nominal stresses generated by the multibody dynamic model to produce local stress time histories. Using these results, a comprehensive fatigue assessment is performed of the 15-MW monopile-based wind turbine, taking into account met-ocean conditions specific to the West Coast of Ireland. This analysis indicates that TMDs have a negative impact on the performance of the turbine in the fore-aft direction which dominates the fatigue loads, resulting in a marginal reduction of the operational lifespan of the wind turbine.
Engineering Materials, Structures, Systems and Methods for a More Sustainable Future
PUBLISHED
London
Keywords: Smart & Sustainable Planet; Renewable energy; Wind Energy and Wind Turbines